Risk Analysis of Murabahah Financing in Barokah Business Capital Products at BMT UGT Sidogiri: A Sharia Microfinance Risk Management Perspective - Nazia, Zumrotun (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
BMT UGT Sidogiri, as a non-bank financial institution operating based on sharia principles, has an obligation to implement risk management in order to minimize potential risks in a measurable and effective manner. Risk management includes establishing risk analysis policies and procedures, determining risk limits, and implementing the process of identifying, measuring, controlling, and monitoring risks. This study aims to analyze the risks of murabahah financing in the Modal Usaha Barokah product and to examine the role model of risk management applied by BMT UGT Sidogiri Capem Karangploso. This research is a qualitative study using a case study approach at BMT UGT Sidogiri Capem Karangploso. Data collection techniques were carried out through observation, interviews, and documentation. The validity of the data was then checked using triangulation techniques. The research results indicate that the Murabahah Financing Risk Analysis process conducted by BMT is not comprehensive, which will certainly have a negative impact on the organization or institution, as well as on financing profitability. This also gives rise to various types of unwanted risks and losses. The incomprehensive implementation of risk management is caused by a lack of human resources (HR) knowledge regarding Islamic financial transactions and a lack of oversight by the Sharia Supervisory Agency (DPS) in overseeing the financing process.